'I just keep thinking I haven't got it because I'm not yellow': a qualitative study of the factors that influence the uptake of Hepatitis C testing by prisoners - Stobbart Lynne; Khaw Fu-Meng; Murtagh Madeleine J (BMC, 2007)
Abstract Background Hepatitis C viral (HCV) infection is a significant public health problem. In the UK, an estimated 200,000 individuals have active HCV infection, most of whom are injecting drug users (IDUs). Many IDUs spend time within the prison system therefore screening for HCV infection in this setting is important. However, uptake of testing within prisons is very low. Methods Qualitative interview study. 30 interviews with 25 male and 5 female prisoners with a history of injecting drug use. Results Personal and institutional barriers to uptake of testing for HCV were identified. Personal barriers included: prisoners' fears and lack of knowledge about HCV, low motivation for testing, lack of awareness about the testing procedure, and concerns about confidentiality and stigma. Institutional barriers included: the prisons' applications procedure for testing, inadequate pre- and post-test discussion, lack of pro-active approaches to offering testing, and lack of continuity of care on discharge and transfer. Conclusion This study highlights potential areas of development in the management of HCV in prisons. Further research is needed to evaluate care pathways for HCV in the prison setting and to develop and assess interventions to improve the uptake of testing for HCV by prisoners.